Pengaruh Brand Image, Harga, Online Customer Review, Terhadap Keputusan Pembelian Produk Sepatu Adidas Di Shopee: (Studi Kasus Pada Mahasiswa Prodi Manajemen Angkatan 2021 Universitas Bhayangkara Jakarta Raya) - Firdauzy, Nurul Syah Nasyid; Bukhari, Eri; Nursal, M. Fadhli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of brand image, price, and online customer reviews on purchase decisions for Adidas shoes through the Shopee platform. The background of the research is based on the intense competition in the sports footwear industry and the high consumer interest in Adidas products. A quantitative approach was used, distributing questionnaires to 171 respondents, who are Management students from the 2021 cohort at Universitas Bhayangkara Jakarta Raya and have purchased Adidas shoes. The independent variables are brand image (X1), price (X2), and online customer reviews (X3), while the dependent variable is purchase decision (Y). Data analysis employed multiple linear regression, with t-test, F-test, and coefficient of determination (R²). The results show that all three independent variables significantly influence purchase decisions, both partially and simultaneously. This study provides practical contributions for businesses in enhancing competitiveness through brand image development, competitive pricing, and effective online review management.